2020
DOI: 10.1177/0954409720923497
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a new code for longitudinal train dynamics simulation

Abstract: Longitudinal train dynamics have a significant impact on both safety and performance of railway systems. Numerical simulation of long heavy haul trains can thus provide essential information for the development of diagnostic and signaling systems as well as coupling elements and braking systems. Long trains are usually modeled by considering only the longitudinal degree of freedom and by adding extra resistant forces to represent the track curvature and gradients. The prediction of in-train forces represents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…At this initial stage of the activity, the simple model briefly described above is developed to check the reliability of the monitoring system. However, an upgrade of the model is planned by combining a detailed multibody model of a single vehicle and a longitudinal train dynamics code, able to better simulate the vehicle dynamics behavior during braking operations [37][38][39][40].…”
Section: Physical Quantity Valuementioning
confidence: 99%
“…At this initial stage of the activity, the simple model briefly described above is developed to check the reliability of the monitoring system. However, an upgrade of the model is planned by combining a detailed multibody model of a single vehicle and a longitudinal train dynamics code, able to better simulate the vehicle dynamics behavior during braking operations [37][38][39][40].…”
Section: Physical Quantity Valuementioning
confidence: 99%
“…The code was validated in previous works [49][50][51] on the four simulation scenarios proposed in the international benchmark of LTD simulators using the laws suggested by the benchmark for the computation of the resistant forces, see Table 1 and equations ( 3) and (6). The code validation showed that the outputs computed by the new code are in good agreement with the other simulators joining the benchmark.…”
Section: Description Of the Ltdpolito Codementioning
confidence: 99%
“…Among other considerations, it should be highlighted that RB power represents part of the total braking effort since ED braking use is limited by the maximum braking power of motors and vehicle speed. The proposed LTD model is 1D, as common to most LTD simulators [34,35] and as suggested by the recently established international benchmark of LTD simulators [36,37]. The model considers both the gravitational force due to track slope and the propulsion resistance, which is the sum of rolling resistances and air resistances.…”
Section: Battery Pack Sizingmentioning
confidence: 99%